An improvement to unified size effect law for intact rock - Masoumi, H.; Arefi, A.; Hagan, P.; Roshan, H.; Sharifzadeh, Mostafa (2017)
© 2017 American Rock Mechanics Association (ARMA). All rights reserved. While rock strength is an important input parameter in geotechnical engineering, the size effect of intact rock samples on strength has long been recognised as an issue. Conventionally, it has been believed that increase in size leads to decrease in strength. A few investigations have reported different trend to that consider conventionally where the uniaxial compressive strength (UCS) follows ascending and descending behaviour. Masoumi et al. [1] investigated this behaviour from analytical and experimental viewpoints that resulted in the formulation of the unified size effect law (USEL) which accounts for the reverse size effect behaviour of intact rocks. A limitation of the current USEL is that at very large sizes, the UCS prediction by USEL tends to zero. This paper outlines an improvement to USEL to overcome this limitation based on the multifractal theory. Attributes of the improved USEL model were highlighted and verified using UCS data from different rock types. Finally, it was demonstrated that there is a good agreement between the improved USEL prediction and the experimental results.